Sonographic Measurement of Visceral Fat and Prediction of Metabolic Syndrome in the Elderly - Chien-Yuan Hung; Chen-Wang Chang; Chih-Jen Chen; Ching-Wei Chang; Hui-Yun Cheng; Ming-Jen Chen (International Journal of Gerontology, 2018)
Summary: Background: Visceral fat is considered important in the pathogenesis of metabolic syndrome (MS). Here, we developed a novel method for determining visceral fat by measuring liver–kidney space (LKS) on abdominal sonography and expanded its utilization in the elderly to predict MS. Methods: To assess the correlation between the LKS and MS, 317 consecutive outpatients scheduled for health evaluation were retrospective analyzed. Anthropometric measurements, blood pressure, fasting blood glucose levels, and lipid profiles were obtained following standard protocols. On sonography, the thickness of visceral fat between the liver and right kidney was measured. We also compared its accuracy to predict MS with sonographic fatty liver changes. A total of 72 elderly patients older than 65 years were evaluated (mean age: 66.02 [65–83]). Results: In the current study, LKS = 4 mm enabled a better prediction of MS. The area under the receiver operating characteristic curve was 0.626. The sensitivity and specificity for the presence of visceral fat to predict MS in the elderly were 0.58 and 0.73, respectively. The accuracy to predict MS was 68.1% for the measurement of visceral fat compared with 59.6% for sonographic fatty liver change in the elderly. Conclusion: Measuring LKS by sonography may be a practical method for evaluating visceral fat in the elderly and for predicting MS better than sonographic fatty liver changes. LKS was more associated with abdominal girth and BMI in the elderly from the study supporting the observation that LKS are well correlated with general adiposity. Keywords: obesity, body mass index, metabolic syndrome, sonography, visceral fat